The Relationship between Processed Food Consumption and Animal Protein Intake with the Incidence of Stunting in Toddlers - Nasir Muna; Sitti Rachmi Misba; Taamu Taamu; Nurfaima Nurfatima (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Many factors can cause stunting; one is the mother's parenting style for toddlers. Parenting is closely related to the mother's level of knowledge. Lack of knowledge causes less maternal parenting. It can increase the risk of stunting events in toddlers. Stunting can have an impact on brain development, both in the short and long term. In the short term, it can affect the cognitive abilities of children. In the long run, it can affect the capacity to be educated and cause the loss of job opportunities with better income. The study aimed to examine the relationship between processed food consumption and animal protein intake, as well as the incidence of stunting in toddlers. The type of research used in this study is research with quantitative kinds, using a correlation analysis research design with a cross-sectional approach. Samples were taken from as many as 42 toddlers using consecutive sampling techniques—data collection using primary data using questionnaires and examinations. Data analysis was done using univariate and bivariate methods with a chi-square test. The results of the study showed that the Chi-Square test results at α = 0.05 obtained a p-value of 0.004. This indicates a relationship between processed food consumption and the incidence of toddler stunting. And the Chi-Square test result at α = 0.05 obtained a p-value of 0.001. This shows a relationship between animal protein intake and the incidence of stunting in toddlers. Health workers should continue to improve health counseling in the community, especially for mothers and expectant mothers related to stunting, to reduce the incidence of stunting, which is very public health.